Prevention of Thrombotic Complications during Hysterectomy among Women with Uterine Fibroids - M. Makarenko (Journal of Global Pharma Technology, 2018)
The aim of our study was to determine the state of hemostasis in women with benign tumors of the uterus during and after surgery. Thrombotic complication is one of the most dangerous problems in surgical, obstetrical and gynecological practice. In operative gynecology one of the most dangerous manifestations is thromboembolism, which can be met from 0, 5 to 6, 4% cases. We examined 153 women with the uterine fibroids. Main group consisted of 38 patients who were operated with the usage of the autologous plasma and control group consisted of 115 patients who were operated without the usage of the autologous plasma. We studied a condition of the system of a hemostasis of women of the main and control groups at all stages of supervision. The study found that women with uterine fibroids are at high risk of thrombotic complications during surgery and in the postoperative period. We came to the conclusion that using autoplasma in gynecological practice is economically beneficial and help to reduce the use of donor blood and its components during the surgical treatment of gynecological patients.Keywords: Uterine fibroids, Autologous plasma, Hemostasis system, Thrombotic complication.